Integrated RNA Sequencing and QTL Mapping to Identify Candidate Genes from Oryza rufipogon Associated with Salt Tolerance at the Seedling Stage - Wang, Shanshan; Cao, Meng; Ma, Xin; Chen, Weikang; Zhao, Jie; Sun, Chuanqing; Tan, Lubin; Liu, Fengxia (Frontiers in Plant Science, 2017)
Soil salinity is a common abiotic stress affecting crop productivity. To identify favorable alleles from wild rice (Oryza rufipogon Griff.) that enhance salinity tolerance of rice (O. sativa L.), a set of introgression lines were developed. The introgression lines were derived from an O. rufipogon accession collected from Chaling (Hunan Province, China) as the donor, and a widely-grown O. sativa indica cultivar 93-11 as the recipient. Through evaluating the salt tolerance of 285 introgression lines at the seedling stage, a total of 10 quantitative trait loci (QTLs) related to salt tolerance were identified on chromosomes 1, 5, 7 and 9–12, with individual QTLs explaining 2–8% of phenotypic variance. The O. rufipogon-derived alleles at four QTLs improved salt tolerance in the 93-11 background. At the same time, a salt-tolerant introgression line, 9L136, was identified and characterized. Compared with the recipient parent 93-11, a total of 1,391 differentially expressed genes (DEGs) were detected specifically in 9L136 between salt stress and normal condition through genome-wide expression analysis. Of these, four DEGs located in the QTL regions carried by 9L136, suggesting that the four genes might be candidates associated with salt tolerance. Both the highly salt-tolerant introgression lines and the favorable O. rufipogon-derived QTLs identified in the present study will provide new genetic resources for improving the resistance of cultivated rice against salinity stress using molecular breeding strategies in the future.